2020
DOI: 10.1177/1756284820946904
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms underpinning the efficacy of faecal microbiota transplantation in treating gastrointestinal disease

Abstract: Faecal microbiota transplantation (FMT) is currently a recommended therapy for recurrent/refractory Clostridioides difficile infection (CDI). The success of FMT for CDI has led to interest in its therapeutic potential in many other disorders. The mechanisms that underpin the efficacy of FMT are not fully understood. Importantly, FMT remains a crucial treatment in managing CDI and understanding the mechanisms that underpin its success will be critical to improve its clinical efficacy, safety and usability. Furt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 113 publications
0
22
0
1
Order By: Relevance
“…Potential factors could be the bacteriophages (Caudovirales) or the metabonomics, especially short-chain fatty acids (SCFAs) (Segal et al, 2020). A study showed a higher success rate of FMT with donor samples containing higher fraction of Caudovirales within the stool virome, and after FMT the abundance of the order of Caudovirales bacteriophages reduced significantly in the recipient's stool (Zuo et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Potential factors could be the bacteriophages (Caudovirales) or the metabonomics, especially short-chain fatty acids (SCFAs) (Segal et al, 2020). A study showed a higher success rate of FMT with donor samples containing higher fraction of Caudovirales within the stool virome, and after FMT the abundance of the order of Caudovirales bacteriophages reduced significantly in the recipient's stool (Zuo et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Intervention aiming to ameliorate this pathological environment with the delivery of targeted beneficial or wholesale bacterial populations in the form of probiotics and faecal microbiota transplantation (FMT), respectively, has been in clinical practice for many years (233,234). The various mechanisms by which probiotics and FMT exert their therapeutic effect has been reviewed in detail elsewhere (235)(236)(237), but centre on their interaction with the host mucosal immune system via MAMPs (238,239) or extracellular vesicles (240)(241)(242), the surrounding microbiota via AMPs (243), Downloaded from http://portlandpress.com/bioscirep/article-pdf/doi/10.1042/BSR20203850/913272/bsr-2020-3850c.pdf by guest on 07 June 2021 microbial cross-feeding (244) or nutrient competition, and their contribution to the broader mucosal metabolic environment (118,148). Here we review the latest developments and innovations in probiotics and FMT.…”
Section: Microbiota-targeted Therapiesmentioning
confidence: 99%
“…The role that FMT plays in restoring colonization resistance via commensal bacteria outcompeting pathobionts for critical nutrients, alteration of pH or oxygen tension, and production of metabolites toxic to them is an another potential contributory mechanism of benefit (Kamada et al, 2013). Supporting this concept, FMT is recognized to restore gut microbial metabolites that are key to gut barrier function (including short chain fatty acids and bile acids) from the low levels found in an antibiotic-exposed gut back to higher levels comparable to healthy stool donors (McDonald et al, 2018;Monaghan et al, 2019;Mullish et al, 2019;Martinez-Gili et al, 2020;Segal et al, 2020). This restoration of gut barrier integrity may limit translocation of pathobionts from the intestinal lumen into the circulation, and therefore reduce the risk of bacteremia.…”
Section: Discussionmentioning
confidence: 99%
“…In mouse models, FMT has been seen to reverse the course of otherwise lethal human bacterial mediated sepsis by enhancing pathobiont clearance via the restoration of host immunity in an interferon regulatory factor 3-dependent manner (Kim et al, 2020). As such, part of the benefit of FMT in this setting may involve gut commensal-mediated immune priming, without necessarily significantly suppressing MDRO that colonize the gut (Allegretti et al, 2019;Woodworth et al, 2019;Segal et al, 2020;Bar-Yoseph et al, 2021;Huus et al, 2021). The role that FMT plays in restoring colonization resistance via commensal bacteria outcompeting pathobionts for critical nutrients, alteration of pH or oxygen tension, and production of metabolites toxic to them is an another potential contributory mechanism of benefit (Kamada et al, 2013).…”
Section: Discussionmentioning
confidence: 99%